Enhanced CO2 electroreduction with metal-nitrogen-doped carbons in a continuous flow reactor. Issue 50 (August 2021) - Duarte, Miguel; Daems, Nick; Hereijgers, Jonas; Arenas-Esteban, Daniel; Bals, Sara; Breugelmans, Tom
Graphical abstract: Highlights: Performance study of different M-N-C sites for the CO2 reduction tested in a flow reactor. High 24 h stability attained at 100 mA cm −2 for all M-N-C. Sn-N-C and Ni-N-C established as promising alternatives for the scalability of ERC. Ni-N-C achieves an overpotential reduction of 250 mV compared to Ag at 200 mA cm −2 . Enhanced productivity of 711 L CO m −2 h −1 and 751 g HCOO- m −2 h −1 . Abstract: As part of a mitigation and adaptation approach to increasing carbon dioxide atmospheric concentrations, we report superior performance of various metal-nitrogen-doped carbon catalysts, synthesized using an easily up-scalable method, for the electrochemical reduction to carbon monoxide and/or formate at industrially relevant current densities up to 200 mAcm −2 . Altering the embedded transition metal (i.e. Sn, Co, Fe, Mn and Ni) allowed to tune the selectivity towards the desired product. Mn-N-C and Fe-N-C performance was compromised by its high CO* binding energy, while Co-N-C catalyzed preferentially the HER. Ni-N-C and Sn-N-C revealed to be promising electrocatalysts, the latter being evaluated for the first time in a flow reactor. A productivity of 589 L CO m -2 h -1 at -1.39 VRHE with Ni-N-C and 751 g HCOO- m -2 h -1 at -1.47 VRHE with Sn-N-C was achieved with no signs of degradation detected after 24 h of operation at industrially relevant current densities (100 mAcm −2 ). Stable operation at 200 mAcm −2 led to turnover frequencies for the production of carbon products of up to 5176 h -1 . These enhanced productivities, in combination with high stability, constitute an essential step towards the scalability and ultimately towards the economical valorization of CO2 electrolyzers using metal-containing nitrogen-doped catalysts.